Web 2.0 Based AVT - Alvin Taufik; Vesalia Widawati (Universitas Bunda Mulia, 2018)
The advances in information and communication technology (ICT) has created an opportunity for better interaction and collaboration. In turns, these web 2.0 technologies have encouraged creativity and participation from its users. One of the areas impacted by this is in language teaching and learning. More researchers are using these web 2.0 technologies in their teaching. This research focuses on the core concept of web 2.0 in the most popular video-based social media that is Youtube. The researcher will investigate the features and elements embedded ad available in Youtube which corresponds to the core concept of web 2.0 of collaboration and interactivity. Furthermore, the researcher will devise methods to integrate such concept in language learning, more specifically, on audiovisual translation. The final results are expected to lay the foundations of further interactivity and collaboration in said subjects, and other subjects in which there are potentials to integrate other web 2.0 technologies.Keywords: web 2.0 technologies, Youtube, interactive, collaboration